1972
DOI: 10.1007/bf01868061
|View full text |Cite
|
Sign up to set email alerts
|

Electrotonic spread of current in monolayer cultures of neonatal rat heart cells

Abstract: The passive electrical properties of neonatal rat heart cells grown in monolayer cultures were determined. Hyperpolarizing current pulses were injected through one microelectrode via an active bridge circuit. Membrane voltage displacements caused by the injected current pulses were measured at various distances from the first with a second microelectrode. Using a modified least-squares method the experimental results were fitted to a Bessel function, which is the steady-state solution of the differential equat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
39
3

Year Published

1975
1975
2008
2008

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 34 publications
1
39
3
Order By: Relevance
“…When dissociated embryonic or neonatal ventricular myocytes are grown in monolayer culture they display synchronous beating (Crill, Rumery & Woodbury, 1959;Harary & Farley, 1963), which has been demonstrated to be the result of electrical coupling mediated by low resistance junctions between myocytes ( M -M junctions), between myocytes and fibroblasts (M-F junctions) and between fibroblasts (F-F junctions) (Crill et al, 1959;Goshima, 1969, Hyde et al, 1969Jongsma & van Rijn, 1972;Sachs, 1976). In this study, it has been shown that under normal ionic conditions both M -M and M -F junctions will also allow the transfer of the dye Lucifer Yellow CH (mol wt 457).…”
Section: Discussionmentioning
confidence: 99%
“…When dissociated embryonic or neonatal ventricular myocytes are grown in monolayer culture they display synchronous beating (Crill, Rumery & Woodbury, 1959;Harary & Farley, 1963), which has been demonstrated to be the result of electrical coupling mediated by low resistance junctions between myocytes ( M -M junctions), between myocytes and fibroblasts (M-F junctions) and between fibroblasts (F-F junctions) (Crill et al, 1959;Goshima, 1969, Hyde et al, 1969Jongsma & van Rijn, 1972;Sachs, 1976). In this study, it has been shown that under normal ionic conditions both M -M and M -F junctions will also allow the transfer of the dye Lucifer Yellow CH (mol wt 457).…”
Section: Discussionmentioning
confidence: 99%
“…Muhicellular, sheet-like preparations ot tissue-cultured cardiac muscle suffer from the same drawbacks as their naturally occurring counterparts: problems arising from the complex geometry of fiber interconnections. These preparations have been treated theoretically as a one-dimensional cell (flat ribbon or cylinder [47,48,51,62]) although perhaps, in some cases, the assembled clusters of myoblasts right have been better described as a thick, plane cell or semi-infinite solid. In addition, such tissue-cultured preparations generally were "contaminated" with nonmuscle cells, and, to further complicate matters, the single-electrode bridge technique was frequently used in some of these studies in a way that was open to the kind of criticism referred to above.…”
Section: Discussionmentioning
confidence: 99%
“…The previously reported values for C,~ vary widely both for naturally occurring cardiac muscle (0.81-13.3 #F.cm -2 [2,3,39,46,50]) and tissuecultured heart cells (1.3-20 #F .cm -2 [48,51]), no doubt for the same reasons mentioned for the equivalently wide variations in R,,. Furthermore, the area of membrane per unit length of the preparations used in these reports may have been in two components, one being in series with a resistance; as a consequence, c,, should vary with the method (e.g.…”
Section: Membrane Capacitancementioning
confidence: 92%
See 1 more Smart Citation
“…Electrophysiological readouts of cellular voltage can be obtained by microelectodes (Jongsma and van Rijn, 1972), multielectrode arrays (Israel et al, 1990), or optical mapping (Fast and Kleber, 1993;Rohr and Salzberg, 1994). Optical mapping makes possible the simultaneous measurement of action potentials from a large number of recording sites, which can be used to generate maps of electrical propagation.…”
Section: Introductionmentioning
confidence: 99%